2016
DOI: 10.1016/j.actbio.2016.01.040
|View full text |Cite
|
Sign up to set email alerts
|

The effects of ethanol on the size-exclusion characteristics of type I dentin collagen to adhesive resin monomers

Abstract: During dentin bonding with etch-and-rinse adhesive systems, phosphoric acid etching of mineralized dentin solubilizes the mineral crystallites and replaces them with bound and unbound water. During the infiltration phase of dentin bonding, solvated adhesive resin comonomers are supposed to replace all of the unbound collagen water and polymerize into copolymers. A recently published review suggested that dental monomers are too large to enter and displace water from tightly-packed collagen molecules. Conversel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 21 publications
0
7
0
2
Order By: Relevance
“…Recent research has revealed that collagen fibrils behave as if they were size-exclusion beads of Sephadex in column chromatography. While molecules with molecular weights smaller than 600 Da can enter collagen, molecules larger than 40 KDa are excluded [196][197][198]. Phosphoric acid, with a molecular weight of 100 Da, is small enough to permeate throughout collagen fibrils, solubilizing both extra-and intrafibrillar mineral, leaving dentin completely demineralized and soft.…”
Section: Calcium-chelation Dry Bondingmentioning
confidence: 99%
“…Recent research has revealed that collagen fibrils behave as if they were size-exclusion beads of Sephadex in column chromatography. While molecules with molecular weights smaller than 600 Da can enter collagen, molecules larger than 40 KDa are excluded [196][197][198]. Phosphoric acid, with a molecular weight of 100 Da, is small enough to permeate throughout collagen fibrils, solubilizing both extra-and intrafibrillar mineral, leaving dentin completely demineralized and soft.…”
Section: Calcium-chelation Dry Bondingmentioning
confidence: 99%
“…Additionally, ethanol soaking could further remove some amounts of remaining water from the intrafibrillar compartment of the collagen molecules as well as the interfibrillar compartment 34,39) . The penetrating ethanol might improve the permeation of primer components into the intrafibrillar compartment of the collagen molecules 40) . Furthermore, it has been speculated that the MPS molecule (molecular weight=234 Da) dissolved in ethanol can also penetrate into the collagen fibrils, where the silanol group would then react with the hydroxyl groups of the fibrils by forming hydrogen bonds 41) .…”
Section: Discussionmentioning
confidence: 99%
“…10,11 The remineralization of hybrid layers with size-exclusion characteristics protected against molecules larger than a 40-kDa protein entering the fibril. 32,33 These prevented activated collagenase from penetrating collagen fibers and contributed to the formation of a nanoscale dentin structure. 34,35 The present study investigated the biomimetic remineralization effect of a treatment containing PVPA on the mechanical properties of interface for a year (Fig.…”
Section: Discussionmentioning
confidence: 99%